ChemInform Abstract: Crystalline and Liquid Structure of Zinc Chloride Trihydrate: A Unique Ionic Liquid. Issue 16 (April 2015) - Wilcox, Robert J.; Losey, Bradley P.; Folmer, Jacob C. W.; Martin, James D.; Zeller, Matthias; Sommer, Roger
Abstract The H2O/ZnCl2 phase diagram is re‐investigated in the vicinity of 75 mol% H2O.